The impact of commodity price volatility on resource intensive economies - Ian Keay (Queen's University, Department of Economics, 2010)
Commodity price volatility is bad for macroeconomic performance. Virtually all empirical studies that document this negative relationship rely on the estimation of aggregate growth equations using cross-section evidence drawn from the post-1970 era. This paper uses a simulation model based on the structure of a dynamic renewable resource model of optimal extraction to determine why commodity price volatility affects investment decisions, production levels, profitability, and ultimately long run growth. The Canadian forestry sector is used as a case study to assess the relative strength of each of these effects. Simulation exercises reveal that commodity price volatility shocks significantly reduce resource firms' equity prices and their demand for reproducible and natural capital. As a result of these changes in the firms' external financing costs and investment incentives, extraction costs rise, output levels and profits fall, and real GDP per capita growth slows.
Keywords: O13; Q23; Q32; 330; commodity price volatility; resource based growth; simulation modeling; Rohstoffressourcen; Preis; Volatilität; Investitionspolitik; Wirtschaftswachstum; Theorie